2022
DOI: 10.25259/ijdvl_843_2021
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate monotherapy versus methotrexate and apremilast combination therapy in the treatment of palmoplantar psoriasis: A prospective, randomised, assessor-blinded, comparative study

Abstract: Background Palmoplantar psoriasis is a chronic debilitating condition which significantly impairs quality of life. Objectives To assess the efficacy and safety of the combination of apremilast and methotrexate compared with methotrexate monotherapy in the treatment of palmoplantar psoriasis. Also, to study the impact on treatment on the Dermatology Life Quality Index and Palmoplantar Quality of Life Index. Methods A total of 64 patients were randomised to two groups in a 1:1 ratio - Group A received both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…1 ). These 17 publications consisted of five placebo-controlled RCTs [ 11 , 12 , 14 – 17 ], one single-arm phase II clinical trial [ 18 ], two randomized methotrexate comparative trials [ 19 , 20 ], six prospective/retrospective cohort studies [ 21 26 ], and three case series [ 27 29 ], totaling 1117 subjects with palmoplantar disease treated with apremilast or placebo. Of the 1117 subjects with palmoplantar disease, 948 cases of PP and 169 cases of PPP were represented.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ). These 17 publications consisted of five placebo-controlled RCTs [ 11 , 12 , 14 – 17 ], one single-arm phase II clinical trial [ 18 ], two randomized methotrexate comparative trials [ 19 , 20 ], six prospective/retrospective cohort studies [ 21 26 ], and three case series [ 27 29 ], totaling 1117 subjects with palmoplantar disease treated with apremilast or placebo. Of the 1117 subjects with palmoplantar disease, 948 cases of PP and 169 cases of PPP were represented.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 publications investigated patients with PP treated with apremilast (APR) including four placebo (PBO)-controlled RCTs [ 11 , 12 , 14 16 ], two randomized methotrexate (MTX) comparative trials [ 19 , 20 ], four prospective/retrospective cohort studies [ 22 24 , 26 ], and two case series [ 27 , 29 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent randomised comparative trial conducted by Hassanandani et al .,[ 20 ] the combination therapy of Methotrexate with Apremilast was found to be more effective than methotrexate monotherapy in achieving a Palmoplantar Physician Global Assessment (PPPGA) score of 0 or 1 at week 16 in patients with palmoplantar psoriasis (baseline PPPGA ≥ 3). The study enrolled a total of 60 patients, and the results indicated that the combination therapy was significantly more effective than the monotherapy in achieving the desired outcome (80.0% vs. 60.0%, respectively; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%